2013
DOI: 10.1016/j.imr.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Digestive system-related pathophysiological symptoms of Sasang typology: Systematic review

Abstract: The purpose of this study was to review clinical studies on digestive system-related pathophysiological symptoms of each Sasang type to obtain the generalizable typespecific clinical features, which are important for the diagnosis of the Sasang type and subsequent disease treatment. Sasang typology and digestive system symptom-related keywords were used to search through eight domestic and foreign databases up to March 2012. The results were organized and analyzed based on four categories [digestive function, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
68
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 21 publications
(73 citation statements)
references
References 11 publications
5
68
0
Order By: Relevance
“…There have been studies on the psychological,5, 6, 7 physical,3, 8 genetic,9, 10 and pathophysiological symptoms 8 of each Sasang type, and these have shown that the biopsychosocial profile of each Sasang type is stable across the lifespan using the Sasang Personality Questionnaire 3 and the ponderal index 4 . The biopsychological distinction between Sasang types may be related to specific mechanisms, such as extroversion and neuroticism, 5 novelty seeking and harm avoidance,6, 11, 12 behavioral activation and inhibition systems (neurotransmitters),3, 12, 13 hypothalamic activity, 4 basal metabolic rate, 4 thyroid activity, 4 and the autonomic nervous system 14, 15, 16.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…There have been studies on the psychological,5, 6, 7 physical,3, 8 genetic,9, 10 and pathophysiological symptoms 8 of each Sasang type, and these have shown that the biopsychosocial profile of each Sasang type is stable across the lifespan using the Sasang Personality Questionnaire 3 and the ponderal index 4 . The biopsychological distinction between Sasang types may be related to specific mechanisms, such as extroversion and neuroticism, 5 novelty seeking and harm avoidance,6, 11, 12 behavioral activation and inhibition systems (neurotransmitters),3, 12, 13 hypothalamic activity, 4 basal metabolic rate, 4 thyroid activity, 4 and the autonomic nervous system 14, 15, 16.…”
Section: Introductionmentioning
confidence: 99%
“…The Sasang TSPS are type-specific clinical symptoms in digestion, sweat, sleep, urination, and defecation, and they are considered important clinical indices for diagnosis, intervention, and prognosis along with the biopsychological traits of each Sasang type 3, 8, 17. As for the underlying physiological systems, the Tae-Yang type is a person with strong sympathetic activation and weak anabolism and energy-storing characteristics, whereas the Tae-Eum type has strong anabolism and energy-saving and weak sympathetic activation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13] The SE type, which is dysfunctional in food intake and digestion, frequently reports chronic indigestion, gastroptosis, and gastroadynamics. 8,12,14,15 Irritable bowel syndrome (IBS) is one of the most common functional gastrointestinal disorders. IBS is characterized by abdominal discomfort or pain, bloating, abnormal stool form, and frequency and changes in bowel habits without an organic disease.…”
mentioning
confidence: 99%